An expanded molecular phylogeny of Plumbaginaceae, with emphasis on Limonium (sea lavenders): Taxonomic implications and biogeographic considerations. Issue 24 (6th December 2018) - Koutroumpa, Konstantina; Theodoridis, Spyros; Warren, Ben H.; Jiménez, Ares; Celep, Ferhat; Doğan, Musa; Romeiras, Maria M.; Santos‐Guerra, Arnoldo; Fernández‐Palacios, Jóse María; Caujapé‐Castells, Juli; Moura, Mónica; Menezes de Sequeira, Miguel; et al.
Abstract: Plumbaginaceae is characterized by a history of multiple taxonomic rearrangements and lacks a broad molecular phylogenetic framework. Limonium is the most species‐rich genus of the family with ca . 600 species and cosmopolitan distribution. Its center of diversity is the Mediterranean region, where ca . 70% of all Limonium species are endemic. In this study, we sample 201 Limonium species covering all described infrageneric entities and spanning its wide geographic range, along with 64 species of other Plumbaginaceae genera, representing 23 out of 29 genera of the family. Additionally, 20 species of the sister family Polygonaceae were used as outgroup. Sequences of three chloroplast ( trnL‐F, matK, and rbcL ) and one nuclear (ITS) loci were used to infer the molecular phylogeny employing maximum likelihood and Bayesian analyses. According to our results, within Plumbaginoideae, Plumbago forms a non‐monophyletic assemblage, with Plumbago europaea sister to Plumbagella, while the other Plumbago species form a clade sister to Dyerophytum . Within Limonioideae, Ikonnikovia is nested in Goniolimon, rejecting its former segregation as genus distinct from Goniolimon . Limonium is divided into two major clades: Limonium subg. Pteroclados s.l ., including L. sect. Pteroclados and L. anthericoides, and L. subg. Limonium . The latter is divided into three well‐supported subclades: the monospecific L. sect. Limoniodendron sister to a clade comprising a mostly non‐Mediterranean subclade and a Mediterranean subclade. Our results set the foundation for taxonomic proposals on sections and subsections of Limonium, namely: (a) the newly described L. sect. Tenuiramosum, created to assign L. anthericoides at the sectional rank; (b) the more restricted circumscriptions of L. sect. Limonium (= L. sect. Limonium subsect. Genuinae ) and L. sect. Sarcophyllum (for the Sudano‐Zambezian/Saharo‐Arabian clade); (c) the more expanded circumscription of L. sect. Nephrophyllum (including species of the L. bellidifolium complex); and (d) the new combinations for L. sect. Pruinosum and L. sect. Pteroclados subsect. Odontolepideae and subsect. Nobiles . Abstract : A large molecular phylogeny of Plumbaginaceae with a focus on Limonium provides new insights into the evolution and systematics of this family. Revisions and additions are proposed for the taxonomic entities of Plumbaginaceae and Limonium .